Meningkatkan Hasil Belajar dan Bernalar Kritis dalam Pendidikan Agama Katolik pada Materi Manusia Sebagai Citra Allah dengan Metode Problem Based Learning Pada Peserta Didik di Kelas VII SMP Negeri 3 Sibolga - Edyolensina Sihotang; Yusmanto Yusmanto; Busri Busri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Learning in Indonesia aims to increase the intelligence of students intellectually and emotionally. The study of Catholicism, as part of ethics, aims to develop human understanding as a unique image of God. Humans have different uniqueness and abilities, which must be developed through various efforts to benefit themselves, their families, and society. This research aims to improve the learning outcomes of grade VII students of SMPN 3 Sibolga on the material "Unique Image of Allah" and develop critical thinking skills with the Problem Based Learning method. This qualitative research uses observation in two cycles, based on the Kemmis and Mc Taggart research model which includes planning, action, observation, and reflection. The results of the study showed an increase in students' critical reasoning skills and learning outcomes from cycle I to cycle II, with the average achievement increasing from 88% in cycle I to 90% in cycle II. This study emphasizes the importance of teachers as facilitators in creating interesting learning, by involving students in discovering new understandings.